Celtic Woman [videorecording (DVD)] : the greatest journey : the essential collection (Celtic Woman Ltd., 2008)
Captures the stunning voices of Lisa, Meav, Chloe, Orla, and Hayley, and the inspired fiddle playing of Mairead performing their most beloved and memorable songs. This essential collection gives new fans the opportunity to catch up on the phenomenal group.